Reading the Archive as a Learning Tool: Qualitative Interpretations of the HMS Centurion’s Encounters in Xiangshan - Zhang, Zhixun (Journal of Qualitative Research in Education, 2025)
This paper investigates the events of 1742–1743 between the British warship HMS Centurion and the maritime communities and governments of Xiangshan (Zhuhai Macau) based on a qualitative case study. The study incorporates the analysis of various primary archival materials such as British naval logs, Qing administrative records and Portuguese/Spanish correspondence, as the main data collection method as the primary data collection method. The purposive maximum variation sampling was used to select documents that represent different attitudes or perspectives, such as the naval, local government, and commercial perspectives, with the aim of not only covering all the aspects of the encounter but also having a broad spectrum of views. The analysis of grounded theory involves the use of open coding initially to determine the initial themes, and then the use of axial coding to determine the relationship between the initial themes. The results show how the interactions were molded through cultural misunderstandings, jurisdictional tensions, and communication barriers. Such categories of themes as the importance of local knowledge systems (fishermen and pilots), the influence of power asymmetries, and the importance of procedural and bureaucratic practices are noted. The paper brings out the pedagogical nature of archival records, showing how the records can be used to provide insights into intercultural learning and historical explanation. This work is relevant to our comprehension of the contact zones of the world and provides a pedagogical solution to the teaching of critical thinking, the ability to take perspectives, and historical literacy at the school level.